2000
DOI: 10.1029/2000jd900499
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal variation of monsoon activities associated with the rainfall over Bangladesh during the 1995 summer monsoon season

Abstract: Abstract. The rainfall over Bangladesh during the 1995 summer monsoon season has been investigated in terms of the intraseasonal variation of monsoon activities. The rainfall over Bangladesh is basically dominated by the north-south oscillation of the monsoon trough. The rainfall increases when the monsoon trough is located at the foot of the Himalayas, because synoptic-scale convective activity is much more vigorous to the south of the monsoon trough axis than to the north of it. In addition, the strong south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 19 publications
6
44
0
Order By: Relevance
“…On the other hand, it was also shown that the lower tropospheric zonal wind was highly correlated with the NEIM rainfall in both July and August. This is consistent with the mechanism of the active and break cycle of the monsoon rainfall over Bangladesh analyzed by Ohsawa et al (2000), associated with the difference in the location of the monsoon trough. During the active periods, the monsoon trough was located along the foot of the Himalayas, though it shifted southward to the Bay of Bengal in the break periods.…”
Section: Impacts Of Wnpm Variability On Neim Rainfallsupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, it was also shown that the lower tropospheric zonal wind was highly correlated with the NEIM rainfall in both July and August. This is consistent with the mechanism of the active and break cycle of the monsoon rainfall over Bangladesh analyzed by Ohsawa et al (2000), associated with the difference in the location of the monsoon trough. During the active periods, the monsoon trough was located along the foot of the Himalayas, though it shifted southward to the Bay of Bengal in the break periods.…”
Section: Impacts Of Wnpm Variability On Neim Rainfallsupporting
confidence: 71%
“…It causes a significant westerly anomaly only in August over the Bengal Plain (Fig. 12), which is a known favorable condition for the active phase of rainfall in Bangladesh and Meghalaya (Ohsawa et al 2000;Murata et al 2008;Fujinami et al 2011). The link between the first and second steps was highly affected by the variability at intraseasonal time scales (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Northeastern Bangladesh, in particular, is known as an area of heavy rainfall. A characteristic of northeastern Bangladesh is the late night-early morning maximum of diurnal precipitation observed by rain gauges, the radar in Dhaka, and a geostationary meteorological satellite (Ohsawa et al 2000(Ohsawa et al , 2001Terao et al 2002;Islam et al 2005). These studies suggest that the late night-early morning maximum precipitation is associated with the Meghalaya Plateau.…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies have shown that the 10-20-day (quasibiweekly) rainfall oscillation, associated with the westwardmoving monsoon lows generated over the Bay of Bengal, is dominant over northeast India, including the Meghalaya Hills and Bangladesh (Ohsawa et al 2000;Murata et al 2007), while the 30-60-day periodicity (known as the MaddenJulian oscillation, MJO) is strongest for areas located in southern India (south of 23°N) (Hartmann and Michelsen 1989;Kripalani et al 2004;Kulkarni et al 2009). We defined excess and deficient monsoon years as one standard deviation departure from the long-term rainfall mean .…”
Section: Propagation Of the High Rainfallmentioning
confidence: 99%